La Création chymique. L’exégèse newtonienne de la Genèse selon la correspondance avec Burnet (1680-1681) - Frédéric Mathieu (Methodos)
In a letter to theologian Thomas Burnet in the early 1680s, Newton suggests a chymical interpretation of the Mosaic account of Creation. He postulates that the System of the World, the Sun, the Earth and its landforms were formed through a succession of separations and coagulations from a “common Chaos”. The seas and the mountains resulted from the irregular coagulation of the parcel of Chaos assigned to our planet, in the same way as a saltpeter solution coagulates. All the transformations of the primeval Chaos are performed by a formative force that played on a large scale the role alchemical theories attributed to ferments. That force is gravitation, which Newton associates in this text with the spirit of God. In this respect, the philosopher’s reconstruction has much in common with the chrysopoetic treatises that develop the analogy between the alchemical Magisterium and Genesis. Newton himself had drafted commentaries around these readings, in a period close to the time of his letter to Burnet.